3D–2D image registration in the presence of soft-tissue deformation in image-guided transbronchial interventions. (1st July 2023) - Vijayan, R; Sheth, N; Mekki, L; Lu, A; Uneri, A; Sisniega, A; Magaraggia, J; Kleinszig, G; Vogt, S; Thiboutot, J; Lee, H; Yarmus, L; et al.
Abstract: Purpose . Target localization in pulmonary interventions (e.g. transbronchial biopsy of a lung nodule) is challenged by deformable motion and may benefit from fluoroscopic overlay of the target to provide accurate guidance. We present and evaluate a 3D–2D image registration method for fluoroscopic overlay in the presence of tissue deformation using a multi-resolution/multi-scale (MRMS) framework with an objective function that drives registration primarily by soft-tissue image gradients. Methods . The MRMS method registers 3D cone-beam CT to 2D fluoroscopy without gating of respiratory phase by coarse-to-fine resampling and global-to-local rescaling about target regions-of-interest. A variation of the gradient orientation ( GO ) similarity metric (denoted G O ′ ) was developed to downweight bone gradients and drive registration via soft-tissue gradients. Performance was evaluated in terms of projection distance error at isocenter (PDEiso ). Phantom studies determined nominal algorithm parameters and capture range. Preclinical studies used a freshly deceased, ventilated porcine specimen to evaluate performance in the presence of real tissue deformation and a broad range of 3D–2D image mismatch. Results . Nominal algorithm parameters were identified that provided robust performance over a broad range of motion (0–20 mm), including an adaptive parameter selection technique to accommodate unknown mismatch in respiratory phase. The G O ′ metric yielded median PDEiso = 1.2 mm, compared to 6.2 mm for conventional GO . Preclinical studies with real lung deformation demonstrated median PDEiso = 1.3 mm with MRMS + G O ′ registration, compared to 2.2 mm with a conventional transform. Runtime was 26 s and can be reduced to 2.5 s given a prior registration within ∼5 mm as initialization. Conclusions . MRMS registration via soft-tissue gradients achieved accurate fluoroscopic overlay in the presence of deformable lung motion. By driving registration via soft-tissue image gradients, the method avoided false local minima presented by bones and was robust to a wide range of motion magnitude.